Municipal wastewater treatment with anaerobic membrane Bioreactors for non-potable reuse: a review - Huang, Yu; Jeffrey, Paul; Pidou, Marc (Taylor & Francis, 2024)
Anaerobic membrane bioreactors (AnMBRs) are seen as a promising technology for application in water reuse schemes. However, the evidence base for their potential and efficacy in this regard is fragmented. We draw together this disparate knowledge base to offer a state of the art review of municipal wastewater treatment with AnMBRs and evaluate the technology’s potential application for water reuse. Water quality regulations and standards from different regions of the world are used as performance metrics to compare and contrast the treatment performance of pilot and laboratory scale AnMBR systems reported in the literature (n = 50). Findings indicate that under stable operation, AnMBRs have the potential to produce water for agricultural reuse. However, without post-treatment, AnMBRs are incapable of delivering water that meets other non-potable reuse standards across a range of important parameters such as COD, BOD5, NH3-N and TP. Analysis of key operational parameters determine the operation of AnMBR for non-potable reuse purpose cover influent water matrix, pH, temperature, hydraulic retention time, system and membrane configuration. An assessment of candidate post-treatment technologies suggests a tradeoff between the cost and effluent quality based on the reuse application requirement. We conclude by discussing a number of challenges and limitations to the use of AnMBRs for reuse applications in order to outline a pathway to maturity for effective treatment trains.
Keywords: Anaerobic; membrane bioreactor; post-treatment; standards; water reuse; Eakalak Khan and Lena Q. Ma; 4004 Chemical Engineering; 40 Engineering; 4011 Environmental Engineering; 6 Clean Water and Sanitation; Environmental Sciences